tính giới hạn

a) $\lim\limits_{x\rightarrow4}\dfrac{\sqrt{2x+8}-4}{x-4}$

b)  $\lim\limits_{x\rightarrow2}\dfrac{x^2-4}{\sqrt{4x+1}-3}$

c)  $\lim\limits_{x\rightarrow2}\dfrac{x-2}{2-\sqrt{x+2}}$

10 tháng 11 lúc 22:15

a: $\lim\limits_{x\rightarrow4}\dfrac{\sqrt{2x+8}-4}{x-4}$

$=\lim\limits_{x\rightarrow4}\dfrac{2x+8-16}{\sqrt{2x+8}+4}\cdot\dfrac{1}{x-4}$

$=\lim\limits_{x\rightarrow4}\dfrac{2\left(x-4\right)}{\sqrt{2x+8}+4}\cdot\dfrac{1}{x-4}$

$=\lim\limits_{x\rightarrow4}\dfrac{2}{\sqrt{2x+8}+4}=\dfrac{2}{\sqrt{2\cdot4+8}+4}$

$=\dfrac{2}{\sqrt{8+8}+4}=\dfrac{2}{4+4}=\dfrac{2}{8}=\dfrac{1}{4}$

b: $\lim\limits_{x\rightarrow2}\dfrac{x^2-4}{\sqrt{4x+1}-3}$

$=\lim\limits_{x\rightarrow2}\dfrac{\left(x-2\right)\left(x+2\right)}{\dfrac{4x+1-9}{\sqrt{4x+1}+3}}$

$=\lim\limits_{x\rightarrow2}\dfrac{\left(x-2\right)\left(x+2\right)}{4\left(x-2\right)}\cdot\left(\sqrt{4x+1}+3\right)$

$=\lim\limits_{x\rightarrow2}\dfrac{\left(x+2\right)\left(\sqrt{4x+1}+3\right)}{4}$

$=\dfrac{\left(2+2\right)\left(\sqrt{4\cdot2+1}+3\right)}{4}=\sqrt{9}+3=6$

c: $\lim\limits_{x\rightarrow2}\dfrac{x-2}{2-\sqrt{x+2}}$

$=\lim\limits_{x\rightarrow2}\dfrac{x-2}{\dfrac{4-x-2}{2+\sqrt{x+2}}}$

$=\lim\limits_{x\rightarrow2}\dfrac{x-2}{2-x}\cdot\left(\sqrt{x+2}+2\right)$

$=\lim\limits_{x\rightarrow2}\left(-\sqrt{x+2}-2\right)$

$=-\sqrt{2+2}-2=-2-2=-4$

Bình luận (0)

Các câu hỏi tương tự
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết